Squeeze Casting of Sic,Fly-Ash Reinforced Aluminium Alloy Hybrid Composites-A Review - et.al, Maraparambil Ramachandran (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aluminum alloys reinforced composite materials have been widely used in automobile, aeronautical and other commercial applications. Aluminum composites are light weight material with high specific strength, specific modulus, stiffness, heat resistant,eco-friendly and have extreme properties so used in large volumes. Due to these circumstances;we have to reduce the price and weight of the composites, improve and increase physical and mechanical properties. One of the ways to reduce the cost of composites is reducing the cost of reinforcement by using cheap, weightless, and easily available materials like fly ash and improving the properties by adding sic. These properties are achieved through the properties intrinsic in them and the size, shape, orientation, weight and distribution. Several casting methods are used by the industries to manufacture the composite products, and each casting method has its own pros and cons. In traditional process, defects of pore formation due to gas, shrinkage porosities are regular and these defects decrease the mechanical properties and integrity of the end product. To overcome such defects,comparatively better squeeze casting method can be implemented.